UPSTAGING, CENTRALITY AND SURVIVAL IN EARLY STAGE NON-SMALL CELL LUNG CANCER VIDEO-ASSISTED SURGERY. (August 2019) - Boada, M.; Guzmán, R.; Montesinos, M.; Libreros, A.; Guirao, A.; Sánchez-Lorente, D.; Gimferrer, JM.; Agustí, A.; Molins, L.
Graphical abstract: Highlights: Centrality is a risk factor for hiliar upstaging. VATS is less frequently used to approach central tumors. When VATS and THO pN0 patients are compared there are no differences in survival. Lower upstaging detection by VATS is related to selection bias. VATS is as effective as THO to detect nodal upstaging. Abstract: OBJECTIVES: Hiliar (pN1) and mediastinal lymph (pN2) nodal upstaging after surgery for early stage (<IIB) non-small cell lung cancer (NSCLC) is a quality marker of surgical lymphadenectomy. It has been suggested that Video-Assisted Thoracoscopic Surgery (VATS) may result in suboptimal lymphadenctomy because nodal upstaging was lower than after open thoracothomy (THO). We sought to: (1) compare the prevalence of nodal upstaging after VATS and THO in NSCLC < IIB; (2) investigate potential risk factors of nodal upstaging; and, (3) assess the impact of nodal upstaging on survival. METHODS: Retrospective analysis of all anatomical resections for NSCLC < IIB in our center (n = 323) from 2011 to 2017. The surgical procedure [THO (60.4%) or VATS (39.4%)] was chosen by the surgeon on the basis of experience and tumor characteristics (centrality and size). RESULTS: Baseline characteristics were similar between the two groups except for larger and more central tumors in THO (p < 0.05). The prevalence of pN1 upstaging was higher after THO (20.5%) than after VATS (8.6%, p < 0.05), but that of pN2 was similar in both groups (6% (THO) and 6.5% (VATS). Tumor centrality was an independent risk factor for pN1. Survival after THO or VATS was similar, irrespectively of nodal upstaging. CONCLUSIONS: In conclusion, VATS is as useful as THO to detect upstaging. Lower upstaging after VATS is attributable to bias selection. Central tumors are more often approached by thoracotomy and centrality is a risk factor for hiliar upstaging.